Pengembangan Fitur Aplikasi X Berbasis Software Development Life Cycle bagi Ibu Milenial dalam Perencanaan Kehamilan dan Keluarga Berencana - Widya, Fina; Kamso, Sudijanto; Prabawa, Artha; Yuswanto, Tri Johan Agus Agus (FORIKES, 2024)
Most women sometimes forget to record and track their menstrual cycles, so some women don't know their fertile period. Women need health-based digital information technology to make it easier to obtain information and knowledge about women's health, pregnancy, and information about parenting, such as in Application X, but until now there is no information system for recording menstrual cycles in this application. This research aimed to develop a menstrual cycle monitoring prototype that can determine a woman's fertile period and menstrual cycle in Application X. This research was implemented using the